2018
DOI: 10.33349/2018.0.4281
|View full text |Cite
|
Sign up to set email alerts
|

Retos para el reconocimiento editorial y científico de las revistas españolas de patrimonio

Abstract: Cuando las revistas científicas de una disciplina permanecen en el tiempo significa que se han consolidado como medio de comunicación para proyectar la actividad y el funcionamiento de una parcela del conocimiento, de sus investigadores e instituciones. A partir de aquí tienen que evolucionar acreditando rigurosos procesos editoriales; posicionando su difusión en sistemas y bases de datos; y penetrando en los indicadores científicos de calidad. Este trabajo estudia las revistas españolas de patrimonio, una esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Considering the coverage by field and subject category, data shows that in terms of subject matter, Social Science and Humanities journals seem to be predominant, as reported by earlier studies (Huang et al, 2017;Ruiz-Pérez and Jiménez-Contreras, 2019) and confirmed here. The present data show that in Law 36 % of the Web of Science listings, in Education & Information, 26 % and in Ethics, Philosophy & Religion, 22 % are in ESCI journals, attesting to the significance of the new index for coverage of certain subject fields.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Considering the coverage by field and subject category, data shows that in terms of subject matter, Social Science and Humanities journals seem to be predominant, as reported by earlier studies (Huang et al, 2017;Ruiz-Pérez and Jiménez-Contreras, 2019) and confirmed here. The present data show that in Law 36 % of the Web of Science listings, in Education & Information, 26 % and in Ethics, Philosophy & Religion, 22 % are in ESCI journals, attesting to the significance of the new index for coverage of certain subject fields.…”
Section: Discussionsupporting
confidence: 89%
“…Beyond the definitions and scope of ESCI, as mentioned in some recent studies, the launch of this product marked an important milestone for Web of Science by incorporating more than 7500 new journals. This has meant an increase of 53% in the Core Collection (Ruiz-Pérez and Jiménez-Contreras, 2019).…”
Section: Introductionmentioning
confidence: 99%